Pentingnya Pendekatan Konstruktivisme Dengan Metode Jigsaw Dalam Pembelajaran Bahasa Indonesia Tingkat SMA - Riskianti, Siti Sofa; Ach. Ziyad Ilmi; Eni Safitri; Qurrotul Aini; Taufiqur Rahman; Lailatul Janna (Gayaku Publisher, 2025)
This research aims to change the traditional learning paradigm system using the lecture method and sitting quietly and listening passively by students. Teachers must make updates to the learning process according to students' needs. Constructivism emphasizes the formation of students' knowledge actively and independently in solving problems and giving meaning to what is being studied. Indonesian language learning must be designed according to the criteria needed to provide an effective contribution to high school level students. The jigsaw method in learning Indonesian is designed to influence interaction patterns between students and teachers. Learning by applying a constructivist approach using the jigsaw method can make students more confident in developing their potential. So that teaching and learning activities are not completely controlled by the teacher in the learning process. Students can create learning experiences through their own observations and experiences. Students will be more enthusiastic and have high motivation to learn due to their curiosity about what they are studying. It is important for teachers to understand this application in order to facilitate effective learning.